1999
DOI: 10.1258/1357633991933404
|View full text |Cite
|
Sign up to set email alerts
|

Virtual microscopy and public-key cryptography for Internet telepathology

Abstract: The Internet is a potentially inexpensive, widely available medium for telepathology, but there are concerns about its reliability and security. Using a digital camera, 41 photomicrographs of transbronchial biopsies, at x 100 optical magnification, were captured and digitized at 2700 x 3400 pixel, 24 bit/pixel resolution. The image files were saved in JPEG format at medium compression, attached to text files with patient information, encrypted for security in the S/MIME format using a digital signature and dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…[12][13][14] Six images from each case were photographed at Cedars Sinai Medical Center by VN, using ϫ100 magnification and tiled into a large image using PhotoShop 4.0 software (Adobe Systems, San Jose, CA) ( Fig. 1).…”
Section: Preparation Of "Virtual Slides" For Telecytologymentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Six images from each case were photographed at Cedars Sinai Medical Center by VN, using ϫ100 magnification and tiled into a large image using PhotoShop 4.0 software (Adobe Systems, San Jose, CA) ( Fig. 1).…”
Section: Preparation Of "Virtual Slides" For Telecytologymentioning
confidence: 99%
“…We report a study of 27 patients with mass lesions of the pancreas with static telecytology using high-resolution digital images and methods of virtual microscopy described previously for the study of skin, gastrointestinal, lung, and other biopsy materials. [12][13][14] …”
mentioning
confidence: 99%
“…Static telepathology (also known as offline or store and forward) by Internet e-mail, is the simplest and least expensive form of telepathology, and has been considered an alternative in human pathology. Most published studies have used surgical pathology specimens, including frozen and paraffin sections [3][4][5][6][7][8][9][10][11][12] ; only a few have considered telecytologic diagnosis. [13][14][15][16][17][18][19][20][21] The aim of this study was to test whether telediagnosis through Internet e-mail could be applied in veterinary diagnostic cytology.…”
mentioning
confidence: 99%
“…Most studies to date in telepathology have been more concerned with assessing the concordance of diagnosis between the original specimen slides and the digitized or photographed versions of them [114]. For the most part, these studies have found concordance rates well above 90%, and telepathology is becoming fairly well established in many clinical settings.…”
Section: Introductionmentioning
confidence: 99%